Influence of THF and THF/SDS on the Kinetics of CO2 Hydrate Formation Under Stirring - Wang, Hongliang; Wu, Qiang; Zhang, Baoyong (Frontiers in Energy Research, 2021)
Hydrate-based gas separation is a potential technology for CO2 recovery and storage, and its products can be used for fire prevention and control in mines. Promoters are often employed to accelerate or moderate hydrate formation. In this study, experiments were performed to examine the effects of different concentrations of the thermodynamic promoter tetrahydrofuran (THF) and kinetic promoter sodium dodecyl sulphate (SDS) on CO2 hydrate formation under stirring. The results showed that THF significantly shortens the induction time of CO2 hydrates; however, because THF occupies a large cavity in the hydrate structure, it also reduces the gas absorption and hydrate formation rate. SDS has no obvious effect on the induction time of hydrates, but it can increase the gas storage density and hydrate formation rate. Using THF and SDS together consumed more CO2 than using THF alone or pure water. The peak gas consumption rate was 2.3 times that of the THF system. The hydrate formation efficiency was improved by including both THF and SDS, which maximised both the hydrate formation rate and total gas uptake.